1988
DOI: 10.1128/mcb.8.9.3955
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of cellular protein-binding sites on the products of early-region 1A of human adenovirus type 5.

Abstract: The binding sites for the 300-, 107-, and 105-kilodalton cellular proteins which associate with human adenovirus type 5 ElA products were studied with ElA deletion mutants. AB appeared to bind to the amino-terminal half of ElA products in regions necessary for oncogenic transformation. These results suggest that these cellular species may be important for the biological activity of ElA products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
235
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(247 citation statements)
references
References 37 publications
11
235
1
Order By: Relevance
“…Additionally, CR1 and CR2 regions have also been strongly implicated in the ability of ElA proteins to bind RB1 (11,64). In this colony assay, we have found that mutants carrying either deletions or substitutions (DCS, GCX, and G3/2) or point mutations (pM933 and pM957) within CR2 had little effect upon the ability to rescue VOL.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Additionally, CR1 and CR2 regions have also been strongly implicated in the ability of ElA proteins to bind RB1 (11,64). In this colony assay, we have found that mutants carrying either deletions or substitutions (DCS, GCX, and G3/2) or point mutations (pM933 and pM957) within CR2 had little effect upon the ability to rescue VOL.…”
Section: Resultsmentioning
confidence: 64%
“…of 105, 107, and 300 kDa (10,11,19,65). The 105-kDa ElA-binding protein is the product of the RB1 gene which is absent or altered in retinoblastomas and other human cancers (12,13).…”
mentioning
confidence: 99%
“…The modular nature of AdE1A has facilitated the mapping of proteinbinding sites and linking of biological functions to particular interactions and therefore to certain regions of E1A. Binding of the Rb family or CBP/p300 is necessary for AdE1A to promote S phase entry, but binding of both sets of proteins is required for AdE1A-mediated transformation (Egan et al, 1988;Jelmsa et al, 1989;Howe et al, 1990;Wang et al, 1993). CR3 contains a zinc (Zn 2 ĂŸ )-finger motif and is the site of interaction with a number of proteins involved in transcriptional regulation (Culp et al, 1988;Geisberg et al, 1994Geisberg et al, , 1995Rasti et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Transformation and immortalization functions of E1A have been localized to CR1 and CR2 (Moran et al, 1986;Lillie et al, 1987), whereas CR3 is known to act as a transcriptional activator of viral and cellular promoters (Green et al, 1983;Kao and Nevins, 1983). The E1A 12S product is capable of physically interacting with and functionally neutralizing all of the pRB family proteins but lacks the transcriptional activation functions provided by the CR3 domain (Egan et al, 1988;Jelsma et al, 1989;Whyte et al, 1989;Cobrinik et al, 1993). Accordingly, we generated stable transfectants that express the E1A 12S product by transfecting pOPTET-E1A12S into 32D-B5 cell, a 32Dcl3-derived transfectant clone that ectopically co-express the tetracycline-repressible transactivator (tTA) and the E. coli lac repressor as described (Figure 2a) (Hoshikawa et al, 1998b).…”
Section: E Ect Of Adenovirus E1a Oncoprotein On G-csf-induced Granulomentioning
confidence: 99%